2021
DOI: 10.5027/andgeov48n3-3362
|View full text |Cite
|
Sign up to set email alerts
|

Local Cuban bentonite clay: composition, structure and textural characterization

Abstract: The Cuban bentonite clays have a specific surface area of 79.9098 m2.g-1, a pore volume of about 0.077612 cm3.g-1 and both isotherms exhibited a hysteresis loop of IV type. X-ray diffractogram of raw bentonite shows that the main mineralogical component is montmorillonite (> 90%). The mineral object study presents the first endothermic peak, characteristic of montmorillonite, in 48.11 ºC and others less accentuated (80.81, 94.01, 119.81 ºC) characteristic of calcium montmorillonite, that corresponds to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…The structural formula for one-layer unit of montmorillonite was determined as (Na3.99Al0.01) (Al1.11Fe 3+ 0.49Mg0.18Ti0.07)(Ca0.24Na0.15K0.01)O10(OH)2. This bentonite are characterized by Quero-Jiménez et al, 2021b; where it was shown that it had low concentrations of heavy metals and the viability of its use as an adsorbent for oil impurities. Samples of 45 mL of crude SLO and the Cuban bentonite clays at conditions stipulated (bentonite dose, time and speed rate) were taking for analysis.…”
Section: Purification Processmentioning
confidence: 99%
“…The structural formula for one-layer unit of montmorillonite was determined as (Na3.99Al0.01) (Al1.11Fe 3+ 0.49Mg0.18Ti0.07)(Ca0.24Na0.15K0.01)O10(OH)2. This bentonite are characterized by Quero-Jiménez et al, 2021b; where it was shown that it had low concentrations of heavy metals and the viability of its use as an adsorbent for oil impurities. Samples of 45 mL of crude SLO and the Cuban bentonite clays at conditions stipulated (bentonite dose, time and speed rate) were taking for analysis.…”
Section: Purification Processmentioning
confidence: 99%